2014
DOI: 10.1177/2150131914546325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Decision Support on the Efficiency of Primary Care Providers in the Outpatient Practice

Abstract: Background: Clinical decision support (CDS) for primary care has been shown to improve delivery of preventive services. However, there is little evidence for efficiency of physicians due to CDS assistance. In this article, we report a pilot study for measuring the impact of CDS on the time spent by physicians for deciding on preventive services and chronic disease management. Methods: We randomly selected 30 patients from a primary care practice, and assigned them to 10 physicians. The physicians were requeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…The WHAT/CDS toolkit was reported to help clinicians prioritize the patients' needs and streamline the patient visit while improving clinician-patient communication. These results were reflective of studies by Wagholikar et al 27 and Edelman et al 11 who found that CDS assistance significantly reduced the time spent by clinicians for deciding on preventive services and chronic disease management while improving delivery of care and enhancing patient engagement.…”
Section: Overall Summarysupporting
confidence: 72%
“…The WHAT/CDS toolkit was reported to help clinicians prioritize the patients' needs and streamline the patient visit while improving clinician-patient communication. These results were reflective of studies by Wagholikar et al 27 and Edelman et al 11 who found that CDS assistance significantly reduced the time spent by clinicians for deciding on preventive services and chronic disease management while improving delivery of care and enhancing patient engagement.…”
Section: Overall Summarysupporting
confidence: 72%
“…In such health care settings, clinical effectiveness refers to the quality of care provided by physicians and registered nurses (e.g., Crosson et al, ) as well as the quality of their clinical decision making (e.g., McGinn et al, ). For its part, clinical efficiency refers to the optimal allocation of resources and competences in clinical processes (e.g., Andersen & Vedsted, ; Schade, Sullivan, de Lusignan, & Madeley, ) and to the cost, time, and workflow constraints of these processes (e.g., Wagholikar et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given the crucial role of organizational innovation in creating a sustainable competitive advantage for business enterprises, its impact upon organizational performance has been previously identified in strategic management research (e.g., Terziovski, ) and IS research in the case of IT‐based innovation (e.g., López‐Nicolás & Meroño‐Cerdán, ; Ordanini & Rubera, ). In primary health care settings, service and process innovations such as e‐prescribing and clinical decision support have been linked to improvements in clinical effectiveness and efficiency (e.g., Schade et al, ; Wagholikar et al, ). Consequently, we formulate our last hypothesis as follows:H8 Higher innovation performance is associated to higher clinical performance.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Several interventional strategies such as computerised alerts, manual (training‐ or feedback‐based), and estimated GFR (eGFR) prompts provided to physicians have been implemented in patients with CKD to reduce inappropriate prescribing (IP) . Although most of these interventions have been applied in hospital settings, clinical decision support systems have proven to be effective in reducing IP in outpatient and primary care practices as well …”
Section: Introductionmentioning
confidence: 99%